Beneficial effects of IT solutions in the sport of table tennis - Péter, K.; Csaba, S. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The attracting and retaining amateur table tennis players requires a completely different approach than the one used in case of active professionals. The motivation for amateurs includes: - spending their leisure time with sport activities - health promotion - and of course, earning prestige in their micro-community by getting good results in tournaments There are several known on the benefits of table tennis, especially among elderly people. Our study shows the possible IT solutions for motivating a delicate, but essential group of the sports audience, which is beneficial for all. It is important for: - the individual for health promotion and sport experience, - the sport federations to reach and rouse a wider crowd, - the national healthcare by reducing healthcare costs. This study is based on data provided by the Csongrád County Table Tennis Federation consisting a 5-year period with participation of 385 people. The basic problem which we search practical answers for: the declining number of amateur players, and the trend of decreasing activity among them. Our goal was/is to reverse this tendency. The software, developed in association with the federation produced measurable results, which opens new horizons for improving the activity of amateur players, mainly by providing a social experience for the participants. We succeeded not only in stopping the above-mentioned decrease, but we were able to attract new groups for the sport. The IT capabilities are still far from being utilized; we see a lot of new possibilities in this development.